Reflex hamstring contraction latency in anterior cruciate ligament deficiency. - Beard, D; Kyberd, P; O'Connor, J; Fergusson, C; Dodd, C (1994)
Decreased dynamic stability of the knee joint associated with functional disability is a feature of anterior cruciate ligament deficiency (ACLD). The purposes of this study were to examine the between-limbs difference in reflex contraction latency of the hamstring muscles in patients with unilateral ACLD and to investigate its relationship with instability and function. Fifty patients with arthroscopically diagnosed unilateral ACLD were measured bilaterally for reflex hamstring contraction latency (RHCL), and 20 normal volunteers were similarly tested. The subjects were measured in a position of single-limb full weight-bearing with the knee flexed 30 degrees. An anteriorly directed shear force was applied to the tibia, and surface electromyographs (EMGs) recorded the activity of the hamstrings in response to the applied force. The latency of contraction was defined as the time from initial tibial movement, identified by accelerometry, to the onset of increased hamstring EMG activity. Both legs were tested and a between-limbs difference was computed. A significant difference in RHCL was found between the limb with ACLD and the control limb. The mean RHCL of the limb with ACLD was nearly double that of the unaffected limb, for a significant mean between-limbs difference (p < 0.05). The mean between-limbs difference for the control subjects was not statistically significant. The conclusion is that patients with ACLD have an increased RHCL of the injured leg. As the RHCL is dependent on proprioceptive activity around the joint, it can be used as a measure of proprioceptive ability. The loss of the neurophysiological protective reflex involving the anterior cruciate ligament and hamstrings in patients with ACLD is likely to be a contributory factor in the decreased joint stability experienced by these patients.